Shear Bond Strength of Composite to Nd-YAG Lased Dentin with and without Dye - H. Kermanshah; MJ Kharazi Fard (Tehran University of Medical Sciences, 2004)
Statement of Problem: The achievement of a good and durable dentin/composite resin bond is an important task in restorative dentistry. The application of acid conditioners and dentin bonding agents is an accepted method to enhance this bond strength. Pretreating of dentin surface by laser irradiation seems to be a supplemental way to obtain better results, since lased dentin is more roughened and has a widest surface area to interact with acid conditioner. Purpose: In this study, the effect of dentin surface pretreating by Nd-YAG laser on dentin/composite shear bond strength was examined. Moreover, the effect of Chinese ink as a surface energy absorber on this value was investigated. Methods and Materials: Thirty-nine freshly extracted human teeth without dentinal caries were collected and their occlusal dentins were exposed using a diamond disk. The collected samples were divided into three identical groups. The dentin surface of the first group was lased by an Nd-YAG pulsed laser (100 mJ, 20 Hz) through a 320 m fiber optic in a swiping movement. In the second group, 10% solution of Chinese ink was applied on the dentinal surface before lasing. The samples of the third group were not lased at all. The dentinal surface prepared by 35% phosphoric acid and Scotchbond MP primer and adhesive. Then, composite resin was cured on dentinal surface. After incubation, in water at 37°C for 24 hours, the samples were tested by Digital Tritest ELE machine. Results: The values of bond strength were 20.83±3.96 MPa, 17.83±3.63 MPa and 19.38±4.88 MPa for the lased, unlased and dye-enhanced groups, respectively. The results were not significant by ANOVA test (=0.05). Although in the Weiboul modulus, the lased group offered better bond strength. Conclusion: Further studies are required to determine whether chemical as well as physical alterations to the dentin surface are induced by laser etching, and whether these influence the performance of the range of dentin bonding systems used currently in clinical practice.